2014
DOI: 10.17725/rensite.0006.201412a.0129
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic systems and means of deliberate impact on physical and biological objects

Abstract: Abstract. Modern development level of generation methods of powerfull electromagnetic impulses and radiation forming ways defines development possibility of wide class of directed energy systems and means. In electromagnetic systems and means impacted on biological objects (human) and environment development area and for force systems in electronic warfare (EW) area the following in most known: electromagnetic means of lethal effect, large power generation means for force systems of EW, electronic means of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The issue of reducing the electromagnetic emissions from radio electronic devices is of great importance due to the negative impact of electromagnetic waves (EMW) of UHF and SHF bands on sensitive radio equipment [1][2][3][4] and the human organism [4][5][6][7][8]. Effective reduction of electromagnetic emission from radio electronic devices can be achieved by placing wide-range radio-absorbing screens (RAS) placed inside the housing of the devices, and these screens provide the necessary level of electromagnetic shielding.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of reducing the electromagnetic emissions from radio electronic devices is of great importance due to the negative impact of electromagnetic waves (EMW) of UHF and SHF bands on sensitive radio equipment [1][2][3][4] and the human organism [4][5][6][7][8]. Effective reduction of electromagnetic emission from radio electronic devices can be achieved by placing wide-range radio-absorbing screens (RAS) placed inside the housing of the devices, and these screens provide the necessary level of electromagnetic shielding.…”
Section: Introductionmentioning
confidence: 99%
“…This is confirmed by the effect of the propagation of short-wave radiation over long distances since the Earth's surface and the layer of the ionosphere form a kind of waveguide. Therefore, the influence of low-frequency cosmic radiation on processes on the surface of the earth is usually not considered, although the decisive role of electromagnetic radiation in biological processes is known [6][7][8]. Our studies [9] show that these ideas are erroneous and under certain conditions (indicated below) the ionosphere is not only permeable to low-frequency electromagnetic radiation, but also plays the role of an amplifier of electromagnetic influence.…”
Section: Introductionmentioning
confidence: 99%